Nontraditional risk factors for cardiovascular disease in patients on peritoneal dialysis - Kosaku Nitta (Renal Replacement Therapy, 2024)
Abstract Patients on peritoneal dialysis (PD) have a high prevalence of cardiovascular complications and are at increased risk of cardiovascular mortality. Dialysis increases the likelihood of developing various cardiovascular complications, including ischemic heart disease, cardiac valvular disease, hypertensive cardiomyopathy, and arrhythmias. However, noncardiac circulatory failure can also occur in the absence of obvious cardiac disease in PD patients as a result of excessive fluid volume. Other important causes of nontraditional circulatory failure in these patients include mineral imbalance and severe anemia. In this review, I focus on nontraditional risk factors for cardiovascular disease in PD patients, including ultrafiltration failure, chronic kidney disease–mineral bone disorders, anemia, inflammation, and sarcopenia.